STRUCTURE CHARACTERIZATION OF CALCIUM DEFICIENT ELEMENT-SUBSTITUTED HYDROXYAPATITE WITH CONSTANT DOPANT RATIO OF DIFFERENT ELEMENTS - & et al., Al-Sabbagh (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
The element-substituted calcium Deficient hydroxyapatite samples were synthesized using liquid-phase precipitation method. Different element ions (Mg+2, Zn+2, and Cu+2) were added at constant ratio (5% wt.). The phase composition of the element-substituted calcium hydroxyapatite samples was investigated by using X-ray diffraction. A comparison with known characteristics of the synthetic ion-substituted forms of hydroxyapatite was conducted. It was determined, that the investigated materials are single-phase solid solutions of the element-substituted hydroxyapatite. By the methods of IR spectroscopy and Raman scattering (RS) it was discovered the dependence of incorporation of the carbonate anion that occupies a positions of phosphorus-oxygen groups in the hydroxyapatite structure as a result of embedding element ions (Zn+2, Cu+2, Mg+2) in the crystal lattice. Besides, It was determined, that the ratio of the intensities for the C03 group mode to the P04 groups mode depended on the nature of the element atom, which replace the calcium in the lattice of HAP, and reduced by substituting the calcium atoms by the atoms of Zn, Cu, and Mg from 0.15 to 0.06. Modeling of the vibration modes of Raman spectroscopy showed that incorporation of carbon atoms to the hydroxyapatite structure correlate with the Zn, Cu and Mg atomic radius, charge, and activity